Study on properties of yak cashmere fiber. Issue 1 (10th March 2021) - Qin, Xiaoxuan; Qu, Lixin
Abstract : Purpose: As one natural fiber, yak cashmere has been used more and more widely on textile processing due to its excellent warmth retention property. Yarn spinning is the first and the most important step of textile processing. Yarn spinning is closely related to the fiber properties. That is, for giving the optimization spinning process of one new fiber, the properties of the new fiber should be studied firstly. Meanwhile, during the studying of the properties of the new fiber, comparative analysis method was usually used. That is, the property of the new fiber was common comparatively analyzed with other fibers. During the comparative analysis, the spinning process can be optimized. Therefore, in the paper, the properties of the yak cashmere were studied in detail and comparatively analyzed. Design/methodology/approach: The brown yak cashmere, cyan yak cashmere, white cashmere fiber, purple cashmere fiber, cyan cashmere fiber, camel hair fiber and mohair fiber, were chosen as the samples. The fiber length, fineness, strength, curls, moisture regain, mass specific resistance, surface morphology, infrared spectrum, melting behavior, thermal weight loss, friction, x-ray, were tested and comparatively analyzed. Findings: It is shown that the compositions of yak cashmere and cashmere are similar, and makes the physical properties of yak cashmere and cashmere fiber similar. Comparing with the mohair, camel hair and cashmere fiber, the average length of yak cashmere is smaller and the dispersion of length distribution is larger, and the dispersion of yak cashmere strength is larger, which makes the yarn spinning of yak cashmere difficult, especially the high count pure yarn. However, comparing with the mohair, camel hair and cashmere fiber, the friction coefficient and friction effect of yak cashmere is larger, and yak cashmere fiber has relatively less curls and larger crimp rate and crimp recovery rate, and can improve the fiber spinnability. Originality/value: In the paper, taking the brown yak cashmere, cyan yak cashmere, white cashmere fiber, purple cashmere fiber, cyan cashmere fiber, camel hair fiber, mohair fibers as the samples, the properties of the yak cashmere were studied in detail. The fiber length, fineness, strength, curls, moisture regain, mass specific resistance, surface morphology, infrared spectrum, melting behavior, thermal weight loss, friction, x-ray, were tested and comparatively analyzed. The studies can establish foundation for the optimization of the yak cashmere spinning process, and also can provide information for the end uses of the fiber.